Ever-ready for action: Spatial effects on motor system excitability. (June 2020) - de Wit, Matthieu M.; Faseyitan, Olufunsho; Coslett, H. Branch
Abstract: Modulation of excitability in the motor system can be observed before overt movements but also in response to covert invitations to act. We asked whether such changes can be induced in the absence of even covert motor instructions, namely, as a function of the location of the hand with reference to the body. Participants received single-pulse TMS over the motor cortex while they placed their contralateral hand (right hand in Experiment 1, left hand in Experiment 2) to the right or left of their body midline, and looked either at or away from their hand. In both experiments, greater excitability was observed when gaze was directed to the right. This finding is interpreted as a consequence of left brain lateralization of motor attention. Contrary to our expectations, we furthermore consistently observed greater excitability when gaze was directed away from the hand. To account for this finding, we introduce the concept of "surveillance attention" which, we speculate, modulates cortical gain, and thereby cortical excitability. Its function is to increase readiness to act in non-foveated regions of space. Such a process confers an advantage in environments, like those in which humans evolved, in which threatening stimuli may appear unexpectedly, and at any time.